Mixotrophic protists and ecological stoichiometry: connecting homeostasis and nutrient limitation from organisms to communities - Schenone, Luca; Aarons, Zoe S.; García-Martínez, Minerva; Happe, Anika; Redoglio, Andrea (Frontiers in Ecology and Evolution, 2024)
In recent decades, there has been a growing recognition that mixotrophy, the ability to utilize both phototrophy and phagotrophy, is more common among plankton than previously assumed. Even though mixotrophs can become highly abundant, especially under nutrient limitation, and significantly alter nutrient cycling and food-web dynamics due to their dual nutritional modes, a comprehensive synthesis from a stoichiometric perspective is still lacking. We conducted a systematic literature review in which we identified over 130 studies that directly relate nutrient ratios to mixotrophic protists at the organism to community scale. By conceptually linking mixotrophy with the concept of ecological stoichiometry, we provide insights into (1) the role of mixotrophic metabolism and nutrient limitation in regulating cellular homeostasis, (2) mixotroph abundance and community scale responses to nutrient limitation, and (3) the specific case of harmful algal bloom forming mixotrophs. On the organism scale, the existing literature points towards a stabilizing effect of mixotrophic metabolism on elemental composition, and the use of grazing as a compensation mechanism under stoichiometric imbalances in the water and prey. At the community scale, mixotrophs were found to increase in abundance relative to strict autotrophs and heterotrophs in nutrient-limited communities, and provide beneficial food for zooplankton grazers by maintaining relatively low and stable stoichiometry. Furthermore, global-scale models and studies of harmful algal blooms reveal the increasing importance of mixotrophs under climate change – highlighting the need for continued research addressing the interactions between mixotrophs and dynamic stoichiometry to understand the impacts of mixotrophs on global nutrient cycles.